Tanggungjawab Pelaku Usaha Terhadap Konsumen yang Mengalami Kerugian Terhadap Makanan Kadarluarsa - Sirait, Rian Mangapul (JURNAL RETENTUM, 2024)
To ensure customer confidence, businesses must provide expiration dates on their products. Consumer rights must be respected in society. Consumer losses from expiring Food businesses must preserve consumer rights as outlined in Law Number 8 of 1999 on Consumer Protection. Regarding the problems stated, who is liable for customer loss due to expired food products? How do accountability and verification systems apply to claims for expired food goods under consumer indemnity.Normative research type legislation. Research indicates that retailers are most responsible for consumer losses due to expired food products, with other businesses potentially liable if they cannot prove fault. Indonesia approved the consumer protection legislation, which establishes the presumption of culpability and a reverse authentication mechanism. According to this idea, a businessman is presumed guilty and must compensate customers unless proven innocent. To show consumer indemnification, the merchant is the one being sued.